USING THE CONFORMITY COMPLEXATION REE IN NITRATE SYSTEMS IN FORMATION OF OXIDE OF CONSTRUCTIONAL MATERIALS ON THEIR BASIS (Збірник наукових праць Галузеве машинобудування будівництво, 2017)
Using the complex of physico-chemical methods the studied the nature and specialfeatures of chemical interaction, thermal transformations (25 – 1000 oC) of structuralcomponents in a model system of neodymium and potassium nitrates – systems of nitrates ofrare-earth elements and elements of periodic system IA group, ammonium, that at present arewidely used in syntheses, technological regulations of creation on their base constructionalmaterials of different designation with the assigned complex of structurally sensitivecharacteristics. A number of special features and regularities in their joint behavior werediscovered.Keywords: neodymium, potassium, nitrates, complexion, coordination compounds,thermal transformations, property.